Tracer Study and User Satisfaction for Alumni of the Sociology and Anthropology Education Study Program of the FISIP UNNES, Indonesia - Husain, Fadly; Wijaya, Atika; Wicaksono, Harto; Fatimah, Nurul; Fauzi, Malik Ridwan; Alias, Nizamuddin (Universitas Negeri Semarang, 2024)
Throughout its journey as an educational forum, the sociology and anthropology education deparment of Universitas Negeri Semarang has graduated 18 batches. The existence of graduates and access to a job must be known by the institution where graduates take their education because the output provided by graduates is a very important indicator of knowing the quality of education organized by the Sociology and Anthropology Education Deparment. The objectives of this study were (1) to determine the absorption of the work field of graduates of the Sociology and Anthropology Education Deparment in 2020-2022, (2) to determine the level of satisfaction of alum users with the performance of graduates of the Sociology and Anthropology Education Deparment in 2020-2022. This research was conducted using a quantitative descriptive approach and cluster sampling technique in sampling. Data was collected using a questionnaire and analyzed using descriptive statistics. The results of the tracer study provide an overview of the 168 alums. 51% of graduates work in education, while as many as 49% work in the non-educational sector, such as entrepreneurs and the government sector. Users of graduates (stakeholders) assessed alum performance with good and very good criteria, especially in the categories of ethics, main competencies, proficiency in the use of information technology, communication, teamwork, and personal development. As many as 21% of the graduates chose to continue their studies. The input submitted was obtained from the existing findings: quality in doing social research, improving foreign language skills, and increasing learning related to religion. This input is given as input for efforts to improve the quality of the next Sociology and Anthropology Education Deparment graduates.